Smart oil palm multi-purpose tractor (prototype) - Zainol @ Abdullah, Wan Nor Zanariah; Mohamad Idris, Zainul Ariffin (Malaysian Society of Agricultural Engineers, 2019)
Advancements in field mechanization for the oil palm industry have improved year by year and urged to the introduction of machines which could be adapted to local usage. A suitable choice of machines is depend on the land size, terrain condition, management practice and economic returns. Recently, mechanization approaches vary from one crop to another crop with the major aim of overcoming labour shortage and to increase the quality of agriculture production. Thus, “Smart Oil Palm Multi-purpose Tractor (SOPMT)” is a multipurpose vehicle designed to perform in all types of terrain, while dutiful of the environment. An articulate 4x4 all-terrain vehicle (prototype) developed with a smart hydraulic system that could work in peat, wet soils and hilly conditions. This tractor offer versatility in performing wide range of tasks which is suitable for harvesting and transporting the fresh fruit bunch (FFB) of oil palm to the implement as well as useful for spraying and applying fertiliser, herbicide, pesticide or insecticide. SOPMT also developed to remove the damaged frond from it trunk and could extremely pull heavy loads. It is also equipped with control chamber that has adjustable sit and digital screen to autonomously control the required tasks. This tractor is of a high standard to solve the harvesting, collection and transportation of FFB. Thus, by using this tractor, it could significantly enhance the quality of labour works as well as the quality of oil palm production.